CITRA TETUNTEL TUNTEL DAN TEGODEK GODEK DALAM CERITA RAKYAT DARI LOMBOK NUSA TENGGARA BARAT KARYA G. PARMAN DAN SLAMET RIYADI ALI - Hilda Hastuti (LPPM Universitas Bumigora Mataram, 2019)
This article examines written literature in Lombok. Written literature is a recording of oral literature which is alive and efflorescent in a society conveyed mouth to mouth (tutur tinular). The corpus of the study was the figure of the Tuntel tuntel and Tegodek godek in the folklore of Lombok West Nusa Tenggara by G. Parman and Slamet Riyadi. This folklore or oral tradition serves as solace, social criticism, and educational tools. The theory used in this research is the literary theory that focuses on the figure, character, mandate, and plot in the story of Tetuntel tuntel and the Tegodek godek. The approach is an intrinsic approach, which is an approach that tries to interpret and analyze literary by simply judging from intrinsic elements or elements in the scope of literary itself without discussing the element out of the literary itself. As the author's background, the literary social situation. The method used is a descriptive method, which is to give an explanation or description of the frog character (Tetuntel Tuntel) and Monkey (Tegodek godek) in the folklore of Lombok, West Nusa Tenggara. The result of this research derived from the beggining, middle, and end of story that the tetuntel tuntel was an honest and kind while Tegodek was a greedy and liar.